2008
DOI: 10.1039/b615629k
|View full text |Cite
|
Sign up to set email alerts
|

Gold catalysis in total synthesis

Abstract: In this tutorial review directed towards chemists interested in synthesis or catalysis, the application of gold catalysis in total synthesis is summarised and the mode of activation of the substrate by the gold catalyst is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
254
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 915 publications
(261 citation statements)
references
References 51 publications
0
254
0
7
Order By: Relevance
“…For a long time, gold was considered to be catalytically rather inactive due to its "chemical inertness", but recent work has demonstrated that gold shows some unexpected and quite novel catalytic activities in both heterogeneous [1] and homogeneous systems [2][3][4][5][6], with a number of potential commercial applications [7]. This has led to an immense increase in research activity in gold catalysis and has been termed the catalytic gold rush [8].…”
mentioning
confidence: 99%
“…For a long time, gold was considered to be catalytically rather inactive due to its "chemical inertness", but recent work has demonstrated that gold shows some unexpected and quite novel catalytic activities in both heterogeneous [1] and homogeneous systems [2][3][4][5][6], with a number of potential commercial applications [7]. This has led to an immense increase in research activity in gold catalysis and has been termed the catalytic gold rush [8].…”
mentioning
confidence: 99%
“…Given their exceptional catalytic features, gold species furthermore outshine other transition metal ion species. For these and other reasons, the number of synthetic methods using gold as a catalyst in recent studies has risen sharply [1][2][3][4][5][6]. However, products obtained by way of gold catalysis-often candidates for certain drugs and medicines-may nevertheless contain gold impurities and thus pose serious health and environmental concerns.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The first breakthrough in gold catalysis occurred in 2000, when Hashmi and coworkers developed a new gold-catalyzed methodology for C-C bond formation. 9 Then onwards, cationic gold species were regarded as the most powerful catalysts for the electrophilic activation of alkynes/allenes/alkenes towards a variety of nucleophiles due to the relativistic effect of gold.…”
Section: Background Of Gold Catalysismentioning
confidence: 99%
“…49,50 Gold complexes are well known for their ability to catalyze a wide variety of synthetically interesting reactions of alkynes/allenes/alkenes. 4,7,28,[51][52][53][54][55][56][57][58] In particular, the gold-catalyzed oxygen transfer of a nucleophilic oxygen atom to an alkyne group is synthetically useful. [59][60][61][62][63][64][65] To further explore the reactivity of Au catalysts towards oxygen-atom transfer reactions, we investigated the gold-catalyzed addition of O-nucleophiles to alkynes to produce synthetically important vinyl ether products in excellent yields and regioselectivities at room temperature.…”
Section: Functionalization Of Alkynes Through Addition Of Nhydroxy Hementioning
confidence: 99%
See 1 more Smart Citation